Changes in the Indian Summer Monsoon during the past 600 years: A high-resolution record from the Anshupa Lake, Upper Mahanadi Delta, Core Monsoon Zone of India. (1st April 2022) - Dash, Chinmay; Shankar, Rajasekhariah; Pati, Pitambar; Rachotappa Manjunatha, Busnur; Ahmad Shah, Rayees; Jose, Jithin
Graphical abstract: Highlights: Indian summer monsoon experienced alternate episodes of high and low rainfall. The little ice age (LIA) was dominated by arid conditions. Dominance of bacterial magnetism during LIA suggest low sedimentation rate. Periodicities in χ lf reaffirm solar influence on Indian summer monsoon. Abstract: The core monsoon zone (CMZ) is an ideal region for reconstructing the Indian summer monsoon rainfall (ISMR). Mineral magnetic and organic geochemical parameters have been measured for an AMS 14 C-dated sediment core from the Anshupa Lake, situated in the eastern part of the CMZ, to reconstruct changes in the paleo-monsoonal precipitation on a sub-decadal scale during the past 600 years. Based on the data obtained, two phases may be recognised in the sedimentation history of the lake over the past six centuries: Phase-I (1397 to 1850 CE) comprising sediments deposited during the Little Ice Age (LIA), and Phase-II (1850 CE to the Present) comprising sediments deposited after the LIA. The measured proxies show decadal to sub-decadal scale variations. The relatively low values of mineral magnetic parameters ( χ lf, χ hf, χ fd, SIRM, χ ARM / χ lf, χ ARM / S I R M, χ ARM / χ lf, and χ ARM / S I R M ) and more positive δ 13 C values during Phase-I suggest a weak ISMR compared to Phase-II. The variations in mineral magnetic parameters suggest that the ISMR was the lowest during the Spörer, Maunder and Dalton Minima, but strong during the intervening periods. This inference resonates with the δ 13 C and C/N profiles of the core. Bacterial magnetite is documented during the mid-16th to mid-17th century, suggesting warm and humid conditions in the intervening phase between the Spörer and Maunder Minima. The magnetic susceptibility ( χ lf ) data exhibit a number of periodicities similar to those shown by cosmogenic nuclide-derived Total Solar Irradiance (TSI) data, reaffirming a solar influence on the Indian summer monsoon in the core monsoon zone of India.